PENGARUH PENGETAHUAN ORANG TUA TERHADAP PERILAKU SWAMEDIKASI ANALGETIKA DI KOTA DENPASAR - Gayatri, Ni Kadek Weni Diah; Suryaningsih, Ni Putu Aryati; Tunas, I Ketut; Ardinata, I Putu Riska (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Self-medication (self-medication) is an effort made by ordinary people to overcome the disease or symptoms of a disease that is experienced by themselves. Analgesics or painkillers are drugs that can reduce pain without reducing consciousness. Knowledge about the use of drugs is low due to the limited knowledge of the community about drugs. Self-medication can be very risky, especially in cases of irresponsible self-medication. This behavior using the Theory of Planned Behavior (TPB) is the result of a modification and development of the previous theory, namely the theory of reasoned action.The purpose of this study was to determine the effect of knowledge level and behavior level on analgesic self-medication.This research was conducted in an observational manner using a Cross Sectional design, in May-June 2023, using a validated questionnaire. A total of 96 respondents who participated, at the level of parental knowledge included in the Fairly Good category of 65.76%, at the level of parental behavior including the positive category of 54 (56.3%). There is a significant influence between the level of knowledge and the level of parental behavior, namely the calculated F value of 25.163 with a p value (0.000) from the Multiple Linear Regression Test Summary Model can explain the magnitude of the value (R) which is equal to 0.460 and obtained (R2) of 0.211 that the effect of the independent variable (Knowledge) on the dependent variable (Behavior) is 21.1%.There is a significant influence between knowledge and behavior in analgetic self-medication for parents of children in Denpasar City. There needs to be counseling and always providing information to the public about the importance of self-medication.